Single-stent strategy for left coronary artery bifurcation lesions in patients with chronic ischemic heart disease: protocol of a randomized trial - S. M. Khokhlunov; G. V. Salamov; Т. V. Kislikhin; E. Yu. Kostyrin; A. I. Tumanov; A. L. Titov; A. A. Patrikeeva (Российский кардиологический журнал, 2023)
Aim. This study aims to compare the intraoperative, immediate postoperative and long-term postoperative results of stenting followed by final kissing balloon angioplasty (FKB) and without FKB for left coronary artery (LCA) bifurcation lesions in patients with chronic ischemic heart disease.Material and methods. We plan to perform an open-label, prospective, randomized, single-center, cohort trial that will include 40 patients with left main coronary artery bifurcation lesion, who will undergo stenting procedure followed by FKB or without FKB, using the second-generation drug-eluting stents. Randomization into two groups will be done after performing coronary angiography, confirming the inclusion criteria and the absence of non-inclusion criteria and signing a written consent in 2 copies. Group 1 — stenting followed by FKB. Group 2 — stenting without FKB. The total follow-up period is 24 weeks. It is planned to contact by phone on 30th and 180th day (±7 days) of postoperative period to obtain the information about patient condition, general survival rate, the events of combined controlled points and drug therapy. During 2d phone contact, on 180th day (±7 days), a patient will be invited to undergo multispiral computed tomography of the coronary arteries.The primary combined end-point: cardiac death, nonfatal myocardial infarction, acute cerebrovascular accident and the repeat target vessel revascularization. The secondary combined end-point: thrombosis and stent restenosis.Conclusion. Our study will optimize the approach to the choice of stenting strategy (with or without FRB) for left main coronary artery bifurcation lesions in patients with chronic ischemic heart disease.